Luminescence variations in cucumber (Cucumis sativus L.) leaves derived from different regeneration systems - Murkowski, A.; Wróblewski, T.; Burza, W.; Skórska, E. (International Journal of Horticultural Science, 1999)
Plants obtained from in vitro culture can show increased susceptibility to environmental stress conditions. In the process of their adaptation to natural conditions it requires monitoring of their physiological state. The methods used to check this phenomenon should estimate quickly and exactly the tolerance to suboptimal environmental factors. Such requirements are satisfied by the methods of measuring chlorophyll luminescence in vivo, e.g. fluorescence induction and delayed luminescence. The objects of our studies were cucumber plants regenerated from cultures of callus and embryogenic cell suspension, as well as the plants obtained from seeds. The plants derived from in vitro cultures displayed a poor physiological condition at the early phase of adaptation characterised by higher susceptibility both to stress caused by increased density of the light flux and low temperature (4 °C) in comparison with the plants obtained from seeds.